Evaluación del comportamiento de la saturación de petróleo actual con base en el análisis de presiones e historia de producción en el campo Ocelote (2016)
This document, propose to evaluate the oil saturation variation, making use of the pressure analysis and production history at Campo Ocelote, based on the pressure data provided by the pressure sensor in the electro-submergible pumping systems (ESP), that are installed on the eighty four producing Wells at Campo Ocelote and the produced flow data of the well´s history, in that order the current oil saturation distribution can be determinate at Carbonera C5 formation and Carbonera C7 formation from a process of dynamic saturations. To finish off, the advantages for HOCOL S.A of having a quality control of the current oil saturation at Campo Ocelote will be financially analyzed.